2010
DOI: 10.1177/0022034510363078
|View full text |Cite
|
Sign up to set email alerts
|

Indian Hedgehog Roles in Post-natal TMJ Development and Organization

Abstract: Indian hedgehog (Ihh) is essential for embryonic mandibular condylar growth and disc primordium formation. To determine whether it regulates those processes during post-natal life, we ablated Ihh in cartilage of neonatal mice and assessed the consequences on temporomandibular joint (TMJ) growth and organization over age. Ihh deficiency caused condylar disorganization and growth retardation and reduced polymorphic cell layer proliferation. Expression of Sox9, Runx2, and Osterix was low, as was that of collagen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
66
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 37 publications
9
66
0
Order By: Relevance
“…We found that Col2-cyan ( fig. 4 ) was localized to the flattened/hypertrophic zones and absent from the upper zones of the mandibular condylar cartilage, which correlated with previous reports on Col2a1 mRNA endogenous gene expression [Shibukawa et al, 2007;Ochiai et al, 2010] in the mandibular condylar cartilage. Gene expression analysis of freshly isolated Col2-cyan cells further supported the expression of Col2-cyan in the flattened/hypertrophic zones.…”
Section: Discussionsupporting
confidence: 90%
“…We found that Col2-cyan ( fig. 4 ) was localized to the flattened/hypertrophic zones and absent from the upper zones of the mandibular condylar cartilage, which correlated with previous reports on Col2a1 mRNA endogenous gene expression [Shibukawa et al, 2007;Ochiai et al, 2010] in the mandibular condylar cartilage. Gene expression analysis of freshly isolated Col2-cyan cells further supported the expression of Col2-cyan in the flattened/hypertrophic zones.…”
Section: Discussionsupporting
confidence: 90%
“…The observation that genetic inactivation of the indian hedgehog (IHH) pathway conveys resistance to degenerative arthritis might be explained by a reduction in the mineral apposition rate of fibrocartilage and articular cartilage 38, 39 or a suppression of the development of osteophytes 40 within the expanded regions of fibrocartilage. That IHH is required for normal formation and maintenance of the chondral fibrocartilage of the TMJ 41, 42 supports this concept. In fact, IHH may be upstream of subsequent cartilage degradation as IHH’s regulation of RUNX2 can lead to increased expression of ADAMTS5, a major protease found in OA cartilage 39 .…”
Section: Discussionmentioning
confidence: 76%
“…19,20 Condylar disorganization, growth retardation, reduced polymorphic cell layer proliferation, and low expression of COL2A1, COL1A1, and SOX9 were found in Ihh-deficient mice from postnatal TMJ. 33 Previous study demonstrated that Ihh acts as a mediator of mechanotransduction, which converts mechanical signals to stimulate cellular proliferation in the condylar cartilage. 34 The high expression of Ihh can also stimulate chondrocyte secretion of PTHrP effectively.…”
Section: Discussionmentioning
confidence: 99%